Pengaruh Sistem Pengendalian Intern dan Ketidakpatuhan pada Peraturan Perundang-undangan Standar Akuntansi Pemerintahan terhadap Opini Audit - Agustiawan, Agustiawan; Putri, Annie Mustika; Simanjuntak, Helkia Yohana (JURNAL AKUNTANSI DAN MANAJEMEN, 2023)
This study aims to examine the effect of the internal control system (SPI), and noncompliance with government accounting standard laws and regulations (SAP) on audit opinions. The sample in this study were auditors at the Riau Province Representative Office of the Audit Board of the Republic of Indonesia (BPK RI Pekanbaru). This research is a quantitative research. This study uses primary data collected using a questionnaire. In this study, the sample was 55 respondents using a saturated sample. The analysis tool used is SPSS 2.6. Based on the results of data analysis, it shows that the Internal Control System (SPI), and Non-Compliance with Government Accounting Standards Legislation (SAP) have an effect on Audit Opinion.